SOCIAL RESPONSIBILITY IN HIGH EDUCATION INSTITUTIONS: EVIDENCE FROM PUBLIC UNIVERSITIES IN CZECH REPUBLIC - KUČEROVÁ Renata; FORMÁNKOVÁ Sylvie; PRÍSAŽNÁ Monika (Journal on Efficiency and Responsibility in Education and Science, 2016)
The present paper shows results of a qualitative survey of corporate social responsibility in the tertiary sector. An example of faculties of economics of public universities in the Czech Republic has been used for assessment of engagement of HEIs in corporate social responsibility activities in the key area covered by ISO 26 000 standard. HEIs in the Czech Republic are engaged in many CSR activities but these activities are often untargeted and representing by-products of other activities. The main drawbacks of all assessed faculties were discovered in the key area KO-5 – environment. The results for the first key area KO-1- organisation governance show that integration of the CSR concept in HEI strategy substantially defines the level of their overall engagement in corporate socially responsible activities.